2009
DOI: 10.1002/ch.371
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality hypnosis

Abstract: Scientific evidence for the viability of hypnosis as a treatment for pain has flourished over the past two decades (Rainville, Duncan, Price, Carrier and Bushnell, 1997;Montgomery, DuHamel and Redd, 2000;Lang and Rosen, 2002;Patterson and Jensen, 2003). However its widespread use has been limited by factors such as the advanced expertise, time and effort required by clinicians to provide hypnosis, and the cognitive effort required by patients to engage in hypnosis.The theory in developing virtual reality hypno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…There are several reasons for integrating VR with established behavioral interventions for pain [2]. First, such a combined intervention may be beneficial for patients who fail to respond to a conventional behavioral treatment such as meditation or hypnosis [27].…”
Section: Potential Applications Of Vr To Persistent Painmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasons for integrating VR with established behavioral interventions for pain [2]. First, such a combined intervention may be beneficial for patients who fail to respond to a conventional behavioral treatment such as meditation or hypnosis [27].…”
Section: Potential Applications Of Vr To Persistent Painmentioning
confidence: 99%
“…First, such a combined intervention may be beneficial for patients who fail to respond to a conventional behavioral treatment such as meditation or hypnosis [27]. Second, VR can standardize the presentation of images, instructions, and environmental sounds used in hypnosis (or other behavioral interventions) for persistent pain [2, 28]. Finally, once patients have achieved enhanced pain control via a combined VR/behavioral intervention protocol, they may be more motivated and more successful with practicing the behavioral intervention on its own in their home environment.…”
Section: Potential Applications Of Vr To Persistent Painmentioning
confidence: 99%
“…Some studies have shown direct effects of gut-directed hypnosis on gastrointestinal (rectal) sensitivity [13,14,16,40], while others could not replicate these findings [15,32,33]. Some investigators have found changes in gastrointestinal motility [16,40,41] while others have not [13,15,42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the effects of clinical hypnosis are similar to intravenous sedation [41], helping to reduce the need for medication during procedures [47][48][49] as well as costs [50]. Unfortunately, clinical hypnosis has had limited development in IO, which has been linked to professionals exposure to X-rays [51], as well as a lack of training and limited standardization of the technique [52][53][54].…”
Section: Clinical Hypnosismentioning
confidence: 99%